Adverse sequelae of the COVID -19 pandemic on mental health services in Chile - Olga Toro-Devia; Camila Solis-Araya; Gonzalo Soto-Brandt; Camilo Sepúlveda-Queipul; Pamela Pino; Franco Loyola; Matías Irarrazaval; Graham Thornicroft; Charlotte Hanlon; Ruben Alvarado-Muñoz (Pan American Health Organization, 2023)
Objective. This study seeks to describe the adverse effects of the COVID-19 pandemic on mental health services in Chile. Methods. This study is part of ongoing multicountry research known as the Mental Health Care - Adverse Sequelae of COVID-19 study (or the MASC study) that includes seven countries. Chile is the only one in Latin America. This study used a convergent mixed methods design. The quantitative component analyzed data about public mental health care collected between January 2019 and December 2021 from the open-access database at the Ministry of Health. The qualitative component analyzed data collected from focus groups of experts that included professionals in charge of mental health services, policy-makers, service users and caregivers. Finally, the data synthesis was performed by triangulation of both components. Results. By April 2020, mental health service provision had been reduced by 88% in primary care; moreover, secondary and tertiary levels had also reduced their mental health activities by, respectively, 66.3% and 71.3% of pre-COVID levels. Negative sequelae were described at the health systems level, and full recovery had not been achieved by the end of 2021. The pandemic affected the essential characteristics of community-based mental health services, with adverse impacts on the continuity and quality of care, reduced psychosocial and community support, and negative effects on health workers' mental health. Digital solutions were widely implemented to enable remote care, but challenges included the availability of equipment, its quality and the digital divide. Conclusions. The COVID-19 pandemic has had significant and enduring adverse effects on mental health care. Lessons learned can inform recommendations for good practices for the ongoing and future pandemics and health crises, and highlight the importance of prioritizing the strengthening of mental health services in response to emergencies.